Callosal misconnectivity and the sex difference in psychosis. - Crow, T; Paez, P; Chance, SA (2007)
The sex difference in age of onset in schizophrenia is paradoxical in the sense that the brain is developing faster in females but onsets are earlier in males. Therefore if schizophrenia, as widely believed, is a disorder of development, the difference is in the wrong direction. Here we attempt to resolve the paradox with the hypothesis that psychosis is an anomaly of development of cerebral asymmetry and the following assumptions: (1) asymmetry (the torque) confers directionality on the 'language circuit'--failure to develop asymmetry leads to the risk of reverse transmission, a putative mechanism of psychotic symptoms; (2) the corpus callosum goes on developing in an antero-posterior direction into the third and fourth decades of life; (3) a sex difference in structure and development of the corpus callosum (with some anterior components greater in males and posterior components greater in females) reflects stronger, faster lateralization in females; (4) because of the inverse relationship between asymmetry and interhemispheric connections, females, by developing faster, avoid the misconnectivity phenomena in the frontal lobes that males, developing more slowly, may encounter at a younger age with particular risk of negative symptoms.